The Mudharabah Implementation in Correlation Context Time Deposit - Asih Untari; Siti Ummu Adillah (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
Islamic banks have the function of collecting funds from customers and channeling funds for real sector activities. One of the legal bases used is Mudarabah. Mudharabah is used as a legal basis for Mudharabah Deposit products which have the aim of collecting customer funds and channeling them into the form of Mudharabah Financing. Both products are offered with a profit sharing system. In Mudharabah Deposits, the customer is a shahibul maal who will get a ratio according to the profit from the Bank. In Mudharabah Financing, the Bank as shahibul maal will get a ratio according to the profit of the Mudharib. Observing further the suitability of Islamic Bank products, especially Mudharabah Deposits and Mudharabah Financing, with the Mudharabah system in the fiqh literature, a sharia study of these products is compiled which is poured into this scientific paper.